The Impact of Training Quality of Life-Based Therapy on Mothers of Children with Autism Spectrum Disorder: A Clinical Trial Study - Sonayaz Hivehchi; Golbahar Akhoundzadeh (مجله دانشگاه علوم پزشکی گرگان, 2024)
Background and Objective: The quality of life of mothers of children with autism spectrum disorder (ASD) is influenced by the problems of this disorder. Numerous interventions have been recommended for mothers with such children, including supportive interventions, cognitive-behavioral therapy (CBT), negative mood management training, parent-child interaction, and family-oriented interventions. One of these interventions is quality of life therapy. The present study was conducted aiming to determine the impact of training quality of life therapy on mothers with ASD children. Methods: This clinical trial was conducted on 60 mothers of 6-13-year-old ASD children referring to the Ofogh Clinic in the city of Gonbad-e-Kavus, Golestan Province, during 2022-23. Mothers were selected by the convenience sampling method and were assigned to two 30-people control and intervention groups using the random number table. The psychotherapy training based on Frisch’s (2006) theory on the quality of life was implemented on mothers in the intervention group as a group in eight 90-minute sessions for two months. The World Health Organization Quality of Life Scale (WHOQOL-BREF) was used to measure the mothers’ quality of life. Results: The mean and standard deviation of the total quality of life score of mothers in the intervention group (76.15±8.85) had a statistically significant increase in the post-test compared to the control group (64.82±10.15) (P<0.05). Also, the mean and standard deviation of the quality of life of mothers in the intervention group showed a statistically significant increase in the post-test in the dimensions of physical health (65.12±6.24), psychological health (69.55±7.52), environmental health (60.66±16.8), and general health (78.33±10.9) compared to the control group (P<0.05). Conclusion: The quality of life of mothers with autistic children was improved by receiving quality of life-based therapy.